Iterative multi‐channel FH‐MFSK reception in mobile shallow underwater acoustic channels. Issue 5 (1st March 2020) - Sun, Dajun; Hong, Xiaoping; Cui, Hongyu; Liu, Lu
Abstract : Frequency‐hopped M‐ary frequency‐shift‐keyed (FH‐MFSK) has the ability to handle with long multipath, large Doppler spreads, high ambient noise and rapid phase fluctuation, and is proved to be a robust modulation scheme in mobile shallow underwater acoustic channels. Aiming at this topic, a convolutionally encoded FH‐MFSK modulation scheme with a novel iterative multi‐channel reception is proposed. To obtain the novel reception suitable for non‐coherent M‐ary frequency‐shift‐keyed, the ideas of iterative multi‐channel demodulation and decoding are combined and extended. A modified multi‐channel soft‐input–soft‐output demodulator based on maximum‐a‐posterior criterion is derived, and substantial gains of several decibels in power efficiency are achieved. Extra gain can be obtained by utilising time diversity with long multipath delay. Simulation shows that a non‐coherent receiver equipped with five arrays obtains around 5.5 dB gain over the single non‐iterative receiver. A shallow water field testing at Songhua Lake with 300 m distance confirms that the proposed receiver verifies its robustness and usability.